Estimation and prediction of avoidable health care costs of cardiovascular diseases and type 2 diabetes through adequate dairy food consumption: a systematic review and micro simulation modeling study - Javanbakht, Mehdi; Jamshidi, Ahmad Reza; Baradaran, Hamid Reza; Mohammadi, Zahra; Mashayekhi, Atefeh; Shokraneh, Farhad; Hamami, Mohsen Rezai; Bakhsh, Raziyeh Yazdani; Shabaninejad, Hossein; Delavari, Sajad; Tehrani, Arash (Academy of Medical Sciences, 2018)
Background: Recent evidence from prospective cohort studies show a relationship between consumption of dairy foods and cardiovascular diseases (CVDs) and type 2 diabetes mellitus (T2DM). This association highlights the importance of dairy foods consumption in prevention of these diseases and also reduction of associated healthcare costs. The aim of this study was to estimate avoidable healthcare costs of CVD and T2D through adequate dairy foods consumption in Iran.